The dual origin of the Palaeohispanic writing systems: A new genealogical model (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work, a new genealogical model for the Palaeohispanic writings is proposed, as the current models does not explain coherently the differences detected between the two Iberian writings. This new model proposes the existence of two intermediate writings between the original Palaeohispanic writing and the documented writings: the original Southern Palaeohispanic writing, to justify the common characteristics of all the southern writings, and the original North-eastern Palaeohispanic script, for the same purpose for the North-eastern writings. In the new model, the orig- inal palaeohispanic writing would have the corresponding syllabic signs only for three vowels. Later, this writing would have undergone two independent adaptations for two different languages that required the creation of new vo- calic signs and new syllabic signs. In addition, the presence of dualities in  the ancient phases of both the North-eastern Iberian and South-eastern Iberi- an writing makes plausible to discard an areal phenomenon and to suggest that this mechanism was already present in its first common ancestor, the original Palaeohispanic writing, and therefore also in the two new intermedi- ate writings.
Keywords: Iberian Script; South-Western Script; Espanca Abecedary; Celtiberian Script; Writing Systems Genealogy